KORELASI DOSIS DAN LAMANYA PENGGUNAAN METADON DENGAN SKOR MEMORI VERBAL PADA PASIEN KETERGANTUNGAN OPIAT YANG MENDAPAT TERAPI RUMATAN METADON - Bambang Pitoyo Nugroho, Mohammad Saiful Islam, Soetjipto (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION METHADONE MAINTENANCE THERAPY IS AN EFFECTIVE THERAPY IN OPIATE DEPENDENCE PATIENTS TO REDUCING DRUG ASSOCIATED HARM HOWEVER THE USE OF METHADONE ALSO ASSOCIATED WITH IMPAIRMENT IN COGNITIVE FUNCTION INCLUDING MEMORY